Effects of Killing Liquids on the Larval Length of Forensically Important Lucilia sericata - Halide Nihal Açıkgöz; Ali Açıkgöz (Adli Tıp Bülteni, 2018)
Objective: Forensic entomological practices rely upon accurate larval identification and measurement of larval length, for the estimation of post-mortem intervals. The methods used for killing larvae may affect the length of larvae. In the autopsy hall, corpses which are contain entomological remains have been washed with grape vinegar. Besides, while collecting and killing the larvae on corpses, crime scene teams use ethanol 70% because it is practical.